2016
DOI: 10.1016/j.neuron.2016.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of High-Frequency Signaling at a Depressing Ribbon Synapse

Abstract: SUMMARY Ribbon synapses mediate continuous release in neurons that have graded voltage responses. While mammalian retinas can signal visual flicker at 80-100 Hz, the time constant, τ, for refilling of a depleted vesicle release pool at cone photoreceptor ribbons is 0.7–1.1 s. Due to this prolonged depression, the mechanism for encoding high temporal frequencies is unclear. To determine the mechanism of high frequency signaling, we focused on an Off cone bipolar cell type in the ground squirrel, the cb2, whose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(70 citation statements)
references
References 67 publications
(105 reference statements)
2
67
0
1
Order By: Relevance
“…The recovery time constant in mouse RBC is 417 ms (Wan et al 2008). Cb2 BC in ground squirrels has a time constant of 70-140 ms (Light and DeVries 2007;Grabner et al 2016), while this number for the Cb3 BC is 524-888 ms (Light and DeVries 2007;Grabner et al 2016) and for the Cb1 is 482-734 ms (Grabner et al 2016). To our knowledge, the recovery time constant of BCs in rabbit and monkey…”
Section: Discussionmentioning
confidence: 86%
“…The recovery time constant in mouse RBC is 417 ms (Wan et al 2008). Cb2 BC in ground squirrels has a time constant of 70-140 ms (Light and DeVries 2007;Grabner et al 2016), while this number for the Cb3 BC is 524-888 ms (Light and DeVries 2007;Grabner et al 2016) and for the Cb1 is 482-734 ms (Grabner et al 2016). To our knowledge, the recovery time constant of BCs in rabbit and monkey…”
Section: Discussionmentioning
confidence: 86%
“…Our results showed that ribbon-mediated release in rods recovered from paired pulse depression with a biexponential time course similar to that observed in cones ( Van Hook et al, 2014 ; Thoreson et al, 2016 ). Under normal circumstances, the principal rate-limiting step that limits synaptic transmission to HCs during sinusoidal stimulation of cones is the fast component of this replenishment process that has a time constant of 600–800 ms ( Innocenti and Heidelberger, 2008 ; Van Hook et al, 2014 ; Grabner et al, 2016 ; Thoreson et al, 2016 ). In both rods and cones, this fast replenishment process involves actions of Ca 2+ operating through calmodulin to enhance vesicle attachment to the ribbon and thereby speed replenishment of ribbon release sites ( Van Hook et al, 2014 ; Van Hook and Thoreson, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the high frequency‐encoding BC type in the ground squirrel expresses high‐affinity glutamate receptors, which saturate quickly and therefore do not profit from a broad glutamate concentration range (Grabner et al . ).…”
Section: Introductionmentioning
confidence: 97%